ANALISIS TITIK PULANG POKOK PADA INDUSTRI TAHUâVIVIâDI KOTA PALU - Murni, Murni; Mapatoba, Marhawati; Laapo, Alimudin (AGROTEKBIS, 2017)
Industry Tofu "Vivi" is an industry engaged in growing small businesses in the city of Palu. Industry Tofu "Vivi" is engaged in agro-industry, that process agricultural commodities such as soybeans into tofu. Industry Tofu "Vivi" is located at Jln. Buah Pala No. 12 Bayoge Village Tatanga Sub District of the City of Palu, Central Sulawesi. This study aims to determine the level of acceptance and the costs incurred by the Industry Tofu s"Vivi" so that the business carried on to reach break-even point. The results of the analysis of break-even point Industry Tofu "Vivi" in January reached when sales volume reached 8.972 kg with admission of Rp. 37.233.800 million, - and for a February break-even point is reached when the sales volume reached 9.258 kg with admission of Rp. 38.420.700.-.Â Keywords: Break even point, Industry Tofu "Vivi", Soybeans